Cross-National variations in mental health: A cross-sectional study on depression, anxiety, and stress among university staff and students in Sub-Saharan African - Oforbuike Onyebuchi Ike; Michael Agyemang Kwarteng; Grace Ogbonna; Isaura Brito dos Santos; Osamudiamen McHillary Ogiemudia; Anayochukwu E. Anyasodor; Ellen Konadu Antwi-Adjei; Okechi Ulumma Amaechi; Ejididke Gertrude Ebele; Ngozika Esther Ezinne; Khathutshelo Percy Mashige; Antor Ndep; et al. (PLoS ONE, 2025)
Purpose Mental health disorders are global concerns, but their impact varies across regions. In sub-Saharan Africa (SSA), the influence of country-specific factors on mental health is under-researched. This study investigates the influence of country of origin on the prevalence and severity of mental health conditions among university students and staff across select SSA countries. Method A cross-sectional, web-based survey using the Depression, Anxiety, and Stress Scale-21 (DASS-21) was conducted from 16 April to 18 November 2024. The survey was distributed online through multiple African social networks, reaching students and staff from different universities across Africa. Prevalence estimates for anxiety, depression, and stress were based on binomial distribution with Clopper-Pearson confidence intervals, while country-level differences were assessed using univariate odds ratios and multiple logistic regression. Results Of the 3221 participants, aged 25.3 ± 8.6 (mean±SD), the majority (1850, 57.3%) were females. Findings revealed that Nigerians reported the highest prevalence of severe and extremely severe mental health conditions, while Ghanaians recorded the lowest levels across all mental health categories. Multivariable analysis revealed that, compared to Ghanaians, respondents from Malawi had the strongest odds for mental health challenges followed by Mozambique and Nigeria. The adjusted odds ratios (AORs) for Malawi were 4.39 (95% CI: 3.28–5.89), 3.86 (95% CI: 2.81–5.29) and 4.51 (95% CI: 3.33–6.11) for depression, anxiety, and stress, respectively. Conclusions This study found significant differences in mental health outcomes between participants from Ghana, Malawi, Mozambique, and Nigeria. Malawi had the greatest risk for depression, anxiety, stress, and combinations of those conditions while Ghana reported the lowest risks. The findings emphasize the importance of considering contextual factors, such as education levels, gender, and country of origin, in understanding mental health risks. Overall, these findings underscore the critical mental health burden in sub-Saharan Africa and the need for increased access to mental health resources and targeted interventions.